Erwägungen Zu Einer Biblischen Hermeneutik - Klein, Hans (Sacra scripta, 2017)
This is an attempt to gather some thoughts about the biblical hermeneutics, from the experiences during and after the repression in the time of the “real socialism”. This needs the understanding of the biblical enunciations, as inspired words for that respective period of time, which, explained can again be inspirational. In order to understand the word of the bible, one has to take into consideration its genus and the social/cultural environment. The teachings of the church and its liturgy are a decisive factor in the elaboration of the hermeneutics.